An assessment of the source potential and reservoir characterization for tight gas exploration in the Subathu Formation shale, Himalayan Foreland Basin, Northwestern India. (1st June 2022) - Hafiz, Mateen; Hakhoo, Naveen; Bhat, Ghulam; Kanungo, Sudeep; Thusu, Bindra; Craig, Jonathan; Ahmed, Waquar; Magotra, Rahul
Graphical abstract: Highlights: The Subathu Formation shales in the Himalayan Foreland Basin (HFB) are analyzed for the source potential and reservoir characterization. The hydrocarbon source potential varies from poor to excellent. Most of the generated hydrocarbons (91%–99%) have migrated. Reservoir characterization shows high clay content (average of 54.5%) in basal part and higher silica content in the middle and top parts of the Subathu Fm. Abstract: The Late Paleocene to Middle Eocene Subathu Formation shales in the prospective Himalayan Foreland Basin (HFB) were investigated to assess their source potential and reservoir characteristics. The organic-geochemical analysis of the investigated samples reveals that the total organic carbon (TOC) content ranges from 0.3 to 42.4 wt%, with an average value of 7.5 wt%. The visual kerogen assessment (VKA), the modified van Krevelen diagram and the HI versus Tmax crossplot indicate the prevalence of type III (gas-prone) kerogen. This is supported by the presence of significant amounts of vitrinite and inertinite group macerals, suggesting deposition in proximity to the source (e.g., swamp forest) in nearshore paludal (marshy) environments. The maximum pyrolysis yield temperature (Tmax) values range between 340 °C and 607 °C, suggesting immature to postmature gas generation stage. The vitrinite reflectance (Ro) values of the basal shale sequence range from 1.16 to 3.6 %, and their high maturity is attributed to their proximity to a major backthrust. The estimated hydrocarbon generation, migration, and retention data suggest a 91%–99% expulsion of hydrocarbons from the Subathu Fm shale. The bulk mineralogical data confirm the dominance of clay minerals (average 54.5%), which decreases up-section, where the younger shales have lesser clays and higher silica content. The kerogen type, richness and level of maturation along with the poor brittleness support a low fracability potential of the basal Subathu shales for tight gas production. A regional comparison is attempted with the Patala Formation in the Potwar Plateau of Pakistan.